Criticism and education: dissatisfaction of parents who homeschool and those who send their children to school with the education system. Issue 6 (2nd November 2019) - Neuman, Ari
ABSTRACT: Homeschooling is a practice in which children of all ages do not attend school, usually by choice of their parents. Research has found diverse reasons for choosing homeschooling, including, reason related to family, personal safety, and others. However, the main reason cited repeatedly for homeschooling is dissatisfaction of parents with the quality of education that children receive at school. The present research used qualitative instruments to examine the criticism of the education system voiced by parents who homeschooled, in comparison with that heard from parents who sent their children to conventional schools. The findings indicate significant differences between the two groups in the nature of their criticism of the education system. The results of the comparison suggest different perceptions of the system and of the purpose of learning. This may enlighten our understanding of the differences among parents who choose different styles of education for their children.